Evaluation of antinutrients in improved and local cultivars of green gram (Vigna radiata (L.) Wilczek) - Sumi Mekkara nikarthil Sudhakaran; Prasanthi Prabhakaran Sobhana; Shreyas Elma Mathew; Devindra Shakappa (Food Chemistry Advances)
Besides being an excellent source of high-quality nutrients, legumes are deposits of antinutritional factors (ANFs) that serve as natural defences against herbivory and pathogens. This investigation aimed to study the concentration of different ANFs in 13 green gram (Vigna radiata (L.) Wilczek) cultivars and explore how varietal differences affect their levels. Ten improved, and three local cultivars of green gram were evaluated for antinutritional content using different spectrophotometric assays. Results revealed variability across cultivars with 0.45 to 1.14 g/100 g of phytic acid, 1.11 to 1.99 g/100 g of saponins, 0.91 to 1.78 mg CE/g of tannins, 17.17 to 25.55 mg GAE/g of total phenolic content, 4.41 to 10.44 TUI/mg of trypsin inhibitors, 0.15 to 0.28 g/100 g of raffinose, 0.14 to 0.36 g/100 g stachyose and 1.60 to 2.88 g/100 g of verbascose. These significant variations highlight the wide range of ANF composition found among green gram cultivars. Such data could aid in exploring the nutraceutical and pharmacological potential of these compounds.